2020
DOI: 10.1001/jamanetworkopen.2020.23663
|View full text |Cite
|
Sign up to set email alerts
|

Association of Chronic Condition Special Needs Plan With Hospitalization and Mortality Among Patients With End-Stage Kidney Disease

Abstract: Key Points Question Is enrollment in a chronic condition special needs plan (C-SNP) associated with improved outcomes in patients with end-stage kidney disease (ESKD)? Findings In this cohort study of 2545 C-SNP enrollees matched at the facility level to patients not enrolled in C-SNP and 1986 C-SNP enrollees matched at the county level to patients not enrolled in C-SNP, C-SNP enrollees had significantly lower hospitalization rates and mortality risk than m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Studies regarding utilisation of healthcare resources for CKD mostly focused on end-stage kidney disease (ESKD). [22][23][24] The US Renal Data System 2019 Annual Data Report showed that the costs for both CKD and ESKD were in excess of $120 billion in 2017, and the latter accounted for more than 7.2% of the total Medicare expenditure. 25 Our study revealed that CKD was associated with a 6.8% increase in costs, which was higher than that of hypertension, diabetes and COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Studies regarding utilisation of healthcare resources for CKD mostly focused on end-stage kidney disease (ESKD). [22][23][24] The US Renal Data System 2019 Annual Data Report showed that the costs for both CKD and ESKD were in excess of $120 billion in 2017, and the latter accounted for more than 7.2% of the total Medicare expenditure. 25 Our study revealed that CKD was associated with a 6.8% increase in costs, which was higher than that of hypertension, diabetes and COPD.…”
Section: Discussionmentioning
confidence: 99%
“…After stage 3, the above symptoms become more obvious, with increased risks of hypertension, heart failure, bone disease, anemia, gastrointestinal symptoms, and a progress to end-stage kidney failure without proper intervention and treatment. [ 5 , 6 ]…”
Section: Introductionmentioning
confidence: 99%
“…After stage 3, the above symptoms become more obvious, with increased risks of hypertension, heart failure, bone disease, anemia, gastrointestinal symptoms, and a progress to end-stage kidney failure without proper intervention and treatment. [5,6] At present, the main principles for CKD are treating original diseases, low-protein diet, essential amino acids intake, and management of complications. Although it could slow down the damage to kidney function, long-term low-protein diet can aggravate malnutrition in patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation